BY ADHERING TO TRADITIONS WE BUILD UP OUR FUTURE OR PLEKHANOV MODEL OF TRADE AND COMMODITY-RESEARCH EDUCATION - Anatoly V. Shishkin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article presents the history of the Plekhanov University from the moment of its formation to the present day. The wonderful traditions, which allowed Plekhanovka to become famous and popular, are highlighted. Special attention is paid to the growth and development of trade and commodity areas of higher education process. The author attempts to connect the Plekhanov educational process in trade area with the main stages of socio-economic development of Russia and specific sectors of its economy. The continuity of traditions, as well as the features of the contemporary model of education process are pointed out.